Análisis de la normativa legal de alojamiento turístico de los hoteles la provincia de El Oro. - Poma Torres, Maritza Abigail (My University, 2018)
The present case study was developed with the purpose of analyzing if the hotel establishments of the Machala canton of the province of El Oro comply with the legal regulations of operation proposed by the Law of the Ministry of Tourism and the tourist accommodation regulations. The data that was obtained through this research were based on the information provided by managers of the five-star hotels in the province of El Oro. For the realization of the present study deductive method was used with the support of a methodological instrument of survey type. Also the study population was made up of the 5 star hotels of the Machala canton of the province of El Oro, the results that were obtained according to the research were that tourist accommodation establishments, if they comply with the legal regulations that allow their operation.
El presente caso de estudio se elaboró con la finalidad de analizar si los establecimientos hoteleros del cantón Machala de la provincia de El Oro cumplen con las normativas legales de funcionamiento que propone la Ley del Ministerio de Turismo y el reglamento de alojamiento turístico. Los datos que se logró obtener por medio de esta investigación fueron en base a la información proporcionada por gerentes de los Hoteles de cinco estrellas de la provincia del El Oro. Para la realización del presente estudio se usaron método deductivo con el apoyo de un instrumento metodológico de tipo encuesta. Asimismo la población de estudio estuvo conformada por los hoteles 5 estrellas del cantón Machala de la provincia de El Oro, los resultados que se obtuvieron de acuerdo a la investigación fueron que los establecimientos de alojamiento turístico, si cumplen con las normativas legales que permiten su funcionamiento.
Keywords: HOTEL; ALOJAMIENTO TURÍSTICO; NORMATIVAS LEGALES; SERVICIOS